Factores sociodemográficos relacionados al dengue en pacientes del Hospital Iquitos César Garayar García Belén 2018 - Garcia Nuñez, Sanam Kalia (2023)
The objective of this investigation was to determine the relationship that exists between sociodemographic factors and dengue in patients hospitalized in the medical service of the Iquitos Cesar Garayar García Belén Hospital, 2018. The method was quantitative with a retrospective correlational non-experimental design. The population consisted of 120 male and female patients with dengue, hospitalized in the medical service (identified through the clinical history); non-probability sampling was used for convenience; The results were: regarding social factors, 80.8% (97) have unhealthy housing, 61.7% (74) adequate storage of water, 88.3% (106) inadequate management of solid waste; Regarding demographic factors, 60.8% (73) are female, 64.2% (77) are adults, 35.0% (42) have completed secondary school, 29.2% (35) have completed primary school, 20.8 % (25) without instruction, 9.2% (11) incomplete secondary, 5.8% (7) incomplete primary; 55.8% (67) are unemployed, 44.2% (53) with work occupation; 55.8% (67) have urban residence, 28.4% (34) peri-urban; 15.8% (19) rural; 69.2% (83) were patients with dengue alarm signs, 25.0% (30) without alarm signs, and 5.8% (7) with severe dengue; When relating the sociodemographic factors and the type of dengue, the type of housing was found p= 0.010; water storage p= 0.000; solid waste management p= 0.001; sex p= 0.037; age p= 0.033, educational level p= 0.036; occupation p= 0.002 and residence p= 0.021 Conclusion: there is a significant and highly significant statistical relationship between the sociodemographic factors and the type of dengue.